Communication of the Movement "Mrican Nagih Promise, Mrican Wegah Diapus" in Rejection of Mrican TPST - Rahmayanti, Dewi Rahmayanti; Huda, Anam Miftakhul (MEDIASI Jurnal Kajian dan Terapan Media, Bahasa, Komunikasi, 2024)
The Mrican final waste disposal site (TPST), which is managed by the Ponorogo Regency Government, experienced overload rubbish and bring a lot of harm to the Mrican community. Rejection of the Mrican TPST is a social phenomenon that emerged as a result of the government's inaction in handling the Mrican TPST. The research examines the "Mrican Nagih Janji, Mrican Wegah Diapusi" movement as the response of the Mrican community to TPST in Mrican which is studied based on the social construction that occurs in the Mrican community. Through a case study approach, this research reveals how social communication plays a role in the social construction process that occurs in Mrican society. By using the case study method [RF1] researchers used observation and in-depth interviews as a way to obtain data. The results of this research show social communication strategies in movements and social construction processes. So with this research we can find out about social communication strategies and social construction processes in Mrican Village.